Trajectory mapping of the early Drosophila germline reveals controls of zygotic activation and sex differentiation - Li, Yi-Ru; Lai, Hsiao Wen; Huang, Hsiao Han; Chen, Hsing-Chun; Fugmann, Sebastian D.; Yang, Shu Yuan (Genome Research, 2021)
Germ cells in Drosophila melanogaster are specified maternally shortly after fertilization and are transcriptionally quiescent until their zygotic genome is activated to sustain further development. To understand the molecular basis of this process, we analyzed the progressing transcriptomes of early male and female germ cells at the single-cell level between germline specification and coalescence with somatic gonadal cells. Our data comprehensively cover zygotic activation in the germline genome, and analyses on genes that exhibit germline-restricted expression reveal that polymerase pausing and differential RNA stability are important mechanisms that establish gene expression differences between the germline and soma. In addition, we observe an immediate bifurcation between the male and female germ cells as zygotic transcription begins. The main difference between the two sexes is an elevation in X Chromosome expression in females relative to males, signifying incomplete dosage compensation, with a few select genes exhibiting even higher expression increases. These indicate that the male program is the default mode in the germline that is driven to female development with a second X Chromosome.
10.1101/gr.271148.120